Japan : Economic and Policy Developments. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2000)
Fiscal policy has been strongly expansionary for most of the past decade in Japan. The resulting strain on public finances has made stimulus policies more difficult to maintain. The stance of monetary policy has remained unchanged over the past year. Further progress in resolving banking problems is essential given the plan to remove blanket deposit insurance in April 2002 and to lay the foundation for sustained growth. The paper discusses recent developments in the field of structural reform and deregulation in Japan.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet